2018
DOI: 10.1111/febs.14586
|View full text |Cite
|
Sign up to set email alerts
|

Cancer: the dark side of wound healing

Abstract: Complex multicellular organisms have evolved sophisticated mechanisms to rapidly resolve epithelial injuries. Epithelial integrity is critical to maintaining internal homeostasis. An epithelial breach represents the potential for pathogen ingress and fluid loss, both of which may have severe consequences if not limited. The mammalian wound healing response involves a finely tuned, self‐limiting series of cellular and molecular events orchestrated by the transient activation of specific signalling pathways. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 188 publications
(209 reference statements)
0
68
0
Order By: Relevance
“…However, chronic and aberrant initiation of wound healing processes has been shown to promote the expansion of cancer cells with stem-like properties that ultimately promote cancer progression. 52 In accordance with this notion, epidemiological studies have shown that higher levels of unconjugated secondary BAs, such as DCA and LCA, in patients who consumed high-fat/low-fiber diets represent risk factors for colorectal cancer development. 53,54 Data from in vitro and in vivo studies have unveiled a paramount role of BAs in promoting the expansion of cancer stem cells (CSCs) in the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 86%
“…However, chronic and aberrant initiation of wound healing processes has been shown to promote the expansion of cancer cells with stem-like properties that ultimately promote cancer progression. 52 In accordance with this notion, epidemiological studies have shown that higher levels of unconjugated secondary BAs, such as DCA and LCA, in patients who consumed high-fat/low-fiber diets represent risk factors for colorectal cancer development. 53,54 Data from in vitro and in vivo studies have unveiled a paramount role of BAs in promoting the expansion of cancer stem cells (CSCs) in the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 86%
“…Immigrated granulocytes stimulated by bacterial endotoxins, fragments of extracellular matrix and cellular detritus secrete a mixture of cytokines and growth factors. In particular, TNFα and interleukin 1β (IL 1β) lead to sustained chronic inflammation [5,7]. In this (micro)environment of chronic inflammation, stimulated mitosis, degradation and regeneration of extracellular matrix lies the cornerstone of abnormal cell proliferation.…”
Section: Pathophysiology In Chronic Woundsmentioning
confidence: 99%
“…Another possible entry point for studying wound repair and its relevance to disease is the role wound repair plays in cancer cell metastasis. As cancer cells invade tissues, they endure plasma membrane stress and damage as they navigate a dense extracellular matrix, and they must quickly heal membrane lesions to avoid excess calcium influx or leakage of cellular content, which both result in cell death [ 37 , 38 , 41 , 42 ]. It has been shown in human breast cancer cells that the S100A2–ANX A2 complex is upregulated, and is necessary for metastasis and invasion [ 124 126 ].…”
Section: Beyond Cellular Repairmentioning
confidence: 99%